PERANAN PEMERINTAH DAERAH TERHADAP PENJUALAN BATIK PRING SEDAPUR DI DESA SIDOMUKTI KECAMATAN PLAOSAN KABUPATEN MAGETAN - Murtiru Murtiru (IKIP PGRI MADIUN, 2016)
This research on the to develop Batik Pring Sedapur sale and role of sales Batik Pring Sedapur sales at Sidomukti village, Plaosan distric, Magetan. This research for answer the problem this research is to know the government role and policy of sales Batik Pring Sedapur sales at Sidomukti village, Plaosan distric, Magetan. Writing this report presented to obtain a qualitative descriptive information about government role of sales Batik Pring Sedapur sales at Sidomukti village, Plaosan distric, Magetan. The method used to collect data is to document study, interviews, observation. The data obtained and analyzed qualitatively with the presented descriptively and then Collecting data and be analized. The results showed that the government has the big role of sales Batik Pring Sedapur sales at Sidomukti village, Plaosan distric, Magetan. The conclusion that can be drawn is increasing Batik Pring Sedapur sale at Sidomukti village, Plaosan distric, Magetan.